2020
DOI: 10.51594/ijarss.v1i3.23
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Unethical Practices by Quantity Surveyors in Nigerian Construction Industry

Abstract: Ethics have a verifiable effect on the validity and economic supportability of quantity studying practices and additionally influencing the individual security of the profession. There is a developing consent inside and outside the construction industry that unscrupulous practices are endemic in the construction industry especially quantity surveying practice in Nigeria. This paper thusly, x-rayed the outcomes of unethical practices by Quantity Surveyors in the construction industry in Nigeria, and likewise di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Where: a=constant expressing the weight assigned to each response (ranges from 1 for No Severe, 2 for less severe, 3 for severe, 4 for very severe and 5 for extremely severe), n=frequency of each response, N=total number of responses [28]. Table 1 above represents the years of operation of the company.…”
Section: S I=mentioning
confidence: 99%
“…Where: a=constant expressing the weight assigned to each response (ranges from 1 for No Severe, 2 for less severe, 3 for severe, 4 for very severe and 5 for extremely severe), n=frequency of each response, N=total number of responses [28]. Table 1 above represents the years of operation of the company.…”
Section: S I=mentioning
confidence: 99%
“…Kasimu, 2016; Adeyemo and Amade, 2016; Ifejike, 2018; Amadi and Higham, 2017; Alolote and Higham, 2018; Ogbu and Asuquo, 2018; Akinrata et al , 2019; Agyekum et al , 2020), though not concerning QS ethical responsiveness on construction projects, except for Akinrata et al (2019) guided the choice of this paper. Akinrata et al (2019) focussed on the results of unethical practices by Nigeria's QS in the industry. They suggested that QSs should not always put financial benefits that would bring doubt to their professional ethics, whilst this paper focusses on the perceived issues that hindered the QSs' ethical responsiveness on construction projects through an in-depth approach (a qualitative mechanism) and proffers initiatives to promote QSs' ethical responsiveness on construction projects in developing country settings, using Nigeria as a case study.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Lee et al (2011) described the services offered by a QS include all aspects of procurement, measuration of works, contractual and project cost management and project documentation, amongst others. Akinrata et al (2019) found clients' dissatisfaction, poor workmanship and high construction cost as the perceived ethical misconduct by QS. The ethical responsiveness of some QSs on construction projects may be doubtful.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite this expectation, the profession is not free of questionable practices. While the profession has gained some attention in past research in Nigeria, most of these studies have been on the implementation of code of ethics, and the prevalence, effects, and outcome of unethical practices within the industry (Olatunji, et al, 2016;Oke, Aghimien and Aigbavboa, 2017;Akinrata and Ogungbile, 2018;Akinrata, Ogunsemi and Akinradewo, 2019;Akpomiemie, Adedokun and Aje, 2018). In a quest to see the reduction of unethical practices within the Nigerian construction industry, this study explored the occurrence of unethical practices among QS, the most prevalent unethical practices, and the possible measures needed to curb these unethical practices.…”
Section: Introductionmentioning
confidence: 99%